2012
DOI: 10.1073/pnas.1202768109
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-finger nuclease-mediated targeted insertion of reporter genes for quantitative imaging of gene expression in sea urchin embryos

Abstract: To understand complex biological systems, such as the development of multicellular organisms, it is important to characterize the gene expression dynamics. However, there is currently no universal technique for targeted insertion of reporter genes and quantitative imaging in multicellular model systems. Recently, genome editing using zinc-finger nucleases (ZFNs) has been reported in several models. ZFNs consist of a zinc-finger DNA-binding array with the nuclease domain of the restriction enzyme FokI and facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Previous studies have reported that simultaneous cleavage of the bait sequences of a donor plasmid and a genomic target site by targetable nucleases can improve the targeted integration efficiency of the plasmid [13, 16]. In our experiments, donor plasmids cleaved by bait systems also showed higher integration efficiencies than that of a donor plasmid with no targeted cleavage (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have reported that simultaneous cleavage of the bait sequences of a donor plasmid and a genomic target site by targetable nucleases can improve the targeted integration efficiency of the plasmid [13, 16]. In our experiments, donor plasmids cleaved by bait systems also showed higher integration efficiencies than that of a donor plasmid with no targeted cleavage (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Although the use of reporter gene imaging for long-term cell tracking in humans is currently restricted by regulatory hurdles, reservations about safety may be addressed by the use of human endogenous versions of reporter genes (e.g., human ferritin reporter for MRI (Campan et al, 2011) and human mitochondrial thymidine-kinase-2 for PET (Ponomarev et al, 2007). To avoid the problem of insertional mutagenesis, safety can be further enhanced by applying newer methods for genomic manipulation such as site-specific integration using phage integrases (Karow et al, 2011; Lan et al, 2012) and safe harbor mediated integration by zinc-finger nuclease (ZFN) (Ochiai et al, 2012; Wang et al, 2012), transcription activator-like effector nuclease (TALEN) (Sommer et al, 2014), or clustered regularly interspaced short palindromic repeats (CRISPR) (Yang et al, 2013). …”
Section: The Future Of Stem Cell Imagingmentioning
confidence: 99%
“…This could be achieved by flanking donor sequences on the injected plasmid by nuclease target sites. Such an approach has been tested in sea urchin and was found to favor HDR in sea urchin embryos injected with ZFNs (Ochiai et al 2012). The use of a circular donor DNA with a nuclease site for in situ linearization but without any homology arms has also been shown recently to result in high-efficiency homology-independent knock-in of in vitro-transfected cells (Cristea et al 2013;Maresca et al 2013) and very recently in zebrafish (albeit concatemers were also observed using this strategy) (Auer et al 2014).…”
Section: Genome Editing In Rats Using Tale Nucleasesmentioning
confidence: 99%